Design and development of mobile EZ-Arabic.Net for ubiquitous learning among Malaysian primary school learners from experts’ perspective - Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal; Abdul Hamid, Mohd Fauzi (Springer Nature, 2018)
Ubiquitous learning, also known as u-learning is based on ubiquitous technology. The most significant role of ubiquitous computing technology in u-learning is to construct a ubiquitous learning environment, which enables anyone to learn at anyplace at any time. This article is focusing on the design and development of a mobile learning platform known as mobile EZ-Arabic.net that serves as a medium of ubiquitous learning in Arabic for Malaysian Primary school learners. The design of this mobile learning application is conducted by transformation a web-based version of EZ-Arabic.net into a mobile application that is suitable for mobile and ubiquitous learning environment. ADDIE model for mobile learning is used for the design and development of this learning platform. The objective of the research is to evaluate a mobile ubiquitous learning platform that was specifically designed for Malaysian primary school learners among subject matter experts (SMEs) from International Islamic University Malaysia (IIUM), Universiti Teknologi MARA (UiTM), Universiti Sains Islam Malaysia (USIM) and Universiti Sultan Zainal Abidin (UniSZA). Based on the findings of the analysis, the learning will be built with content appropriate to meet with students’ needs and syllabus. The final evaluation is also to be conducted among teachers and learners for the improvement of this mobile learning application.